Responses of Linear and Cyclic Electron Flow to Nitrogen Stress in an N-Sensitive Species Panax notoginseng - Cun, Zhu; Wu, Hong-Min; Zhang, Jin-Yan; Shuang, Sheng-Pu; Hong, Jie; Chen, Jun-Wen (Frontiers in Plant Science, 2022)
Nitrogen (N) is a primary factor limiting leaf photosynthesis. However, the mechanism of N-stress-driven photoinhibition of the PSI (photosystem I) and PSII (photosystem II) is still unclear in the N-sensitive species such as Panax notoginseng, and thus the role of electron transport in PSII and PSI photoinhibition needs to be further understood. We comparatively analyzed photosystem activity, photosynthetic rate, excitation energy distribution, electron transport, OJIP kinetic curve, P700 dark reduction and antioxidant enzyme activities in low N (LN), moderate N (MN) and high N (HN) leaves treated with DCMU [3-(3,4-dichlorophenyl)-1,1-dimethyl urea)] and MV (methyl viologen). The results showed that the increased application of N fertilizer significantly enhance leaf N contents and specific leaf N (SLN). Net photosynthetic rate (Pn) was lower in HN and LN individuals than in MN ones. Maximum photochemistry efficiency of PSII (Fv/Fm), maximum photo-oxidation P700+ (Pm), electron transport rate of PSI (ETRI), electron transport rate of PSII (ETRII) and plastoquinone (PQ) pool size were lower in the LN individuals. More importantly, K phase and cyclic electron transport (CEF) were higher in the LN plants. Additionally, there was not a significant difference in the activity of antioxidant enzyme between the MV- and H2O-treated plants. The results obtained suggest that the lower linear electron flow (LEF) leads to the hindrance of the formation of pH and ATP in LN individuals, thereby damaging the donor side of the PSII OEC (oxygen-evolving complex). The over-reduction of PSI acceptor side is the main causes of PSI photoinhibition under LN condition. Higher CEF and antioxidant enzyme activity not only protected PSI from photodamage but also slowed down the damage rate of PSII in P. notoginseng grown under LN.